Gonadal Histology and Expression Analysis of Sex Characteristic Genes in Grass Carp at Different Ages - Bo QI; Shengjie LI; Jinxing DU; Xiaofang XIAO; Dongyun ZHANG; Tao ZHU; Caixia LEI; Zhijun LIU; Hongmei SONG (Progress in Fishery Sciences)
Grass carp belongs to Cypriniformes, Cyprinidae, and Cyprinus family, and is typically referred to as the four famous domestic fishes, black carp, silver carp, and bighead carp, respectively. The annual production of Chinese grass carp is consistently among the highest, with an output of 5.905 million tons in 2022, accounting for 24.3% of total of freshwater fish production. Reproduction is the core process of fish reproduction. Normal gonad development is a prerequisite for fish reproduction. At present, there are few reports on the sex differentiation of Chinese grass carp. Studying the differentiation and development of grass carp gonads can provide a typical model for gonadal development of cyprinid fish. In contrast, the start and completion time of gonadal differentiation are one of the key factors inducing sex reversal in fish using hormones. Research on gonadal differentiation and development in grass carp can also lay the foundation for the establishment of a unisexual population of grass carp.Sex-related genes play important roles in biological processes such as sex determination, gonadal differentiation, and reproduction and development in fish. In most differentiated teleost fish, genes such as dmrt1, sox9, foxl2, amh, and cyp19a1a, are considered the key genes involved in sex regulation. cyp19a1a plays a key role in the gonadal differentiation and ovarian development of teleost fish by aromatizing androgens into estrogen via aromatase activity. This gene is specifically expressed in the gonads and is used served as a characteristic gene for sex differentiation towards females. Anti-Müllerian hormone (amh) regulates the structure of reproductive organs and the differentiation and development of reproductive cells. In fish such as carp, rainbow trout, and grass carp, the expression level of the amh gene in the testes is significantly higher than that in the ovaries, and is often used as a characteristic gene for male differentiation.To explore the sex differentiation and developmental patterns of grass carp gonads, this study analyzed the tissue structure and expression differences of sex characteristic genes cyp19a1a and amh in the gonads of grass carp at 1, 2, 3, 4, 5, 6, 12, 24, 36, and 48 months of age using tissue sectioning technology and real-time fluorescence quantification technology. The results of tissue sectioning showed that grass carp exhibited reproductive ridges at 1-month-old. At 2 months of age, primitive germ cells were first observed in the reproductive crest, marking the formation of their primitive gonads. At 3-month- old, ovarian cavities and lobules were observed in the gonads of female grass carp. At 4-month-old, oogonia was observed, indicating anatomical differentiation at 3-month-old and cytological differentiation at 4-month-old. At the age of 4 and 5 months, ductus deferens and spermatogonia were respectively observed in male grass carp gonads, indicating anatomical differentiation at 4 months and cytological differentiation at 5 months. The ovaries of 24, 36, and 48-month-old grass carp were in the first, second, third, and fourth stages of development, respectively, while the testes were in the second, second, third, and fourth stages of development, respectively. At 48 months of age, the gonads of grass carp have matured. The fluorescence quantitative results showed that the expression level of the female characteristic gene cyp19a1a in the ovary showed an overall trend of first increasing, then decreasing, and then increasing again. The expression level of this gene was significantly upregulated at 2 months of age (P < 0.05), and reached its peak at 3, 6, and 48 months of age. During these three periods, anatomical changes were observed in the female gonads in the tissue sections, with a large proliferation of oocytes and the gonads tending to mature. The expression level of the male characteristic gene amh in the testes showed an overall trend of first increasing and then decreasing. At 2 months of age, the expression level of this gene was significantly upregulated (P < 0.05). At 5 months of age, it reached the peak when there were a large proliferation of spermatogonia in the gonads, and then remained low expression until gonadal maturity.In summary, this study confirmed that the initiation time of grass carp gonadal development is approximately 2 months old, and the differentiation time of male and female gonads is approximately 3 and 4 months old, respectively. By the age of 6 months, both male and female grass carp gonads completely differentiated. These results not only enrich the reproductive physiology data of grass carp but also provide a reference basis for the study of hormone-induced sex reversal technology in grass carp.